Books and periodicals in Brazil 1768-1930
1 online resource (xii, 282 pages)
Keywords: "Before the Portuguese Royal Court moved to its South-American colony in 1808, books and periodicals had a very limited circulation there. It was only when Brazilian ports were opened to foreign trade that the book trade began to flourish, and printed matter became more easily available to readers, whether for pleasure, for instruction or for political reasons. This book brings together a collection of original articles on the transnational relations between Brazil and Europe, especially England and France, in the domain of literature and print culture from its early stages to the end of the 1920s. It covers the time when it was forbidden to print in Brazil, and Portugal strictly controlled which books were sent to the colony, through the quick flourishing of a transnational printing industry and book market after 1822, to the shift of hegemony in the printing business from foreign to Brazilian hands at the beginning of the twentieth century."--Page 4 of cover.